Taking business intelligence to business education curriculum: graduate students’ concerns - Kissi, Philip; Nat, Muesser; Idowu, Adeleye (Business, Management and Economics Engineering, 2017)
Business intelligence systems are widely employed in industries. However, students concerns about Business Intelligence course are largely missed in the business education curriculum. To take a proper decision on Business intelligence integration in business education, it is important to understand students’ concerns. This study employed a survey questionnaire to investigate 142 graduate students concerns about integrating business intelligence into business education curriculum. The survey questionnaire was adopted from previous studies to measure students’ concerns on a Business Intelligence job opportunity, interest and relevance in the Business intelligence education. The survey items have a reliability scales of Cronbach’s alpha (α) = 0.818, factor loading > 0.5, and Average Variance Extracted (AVE) ≥ 0.5, and Composite Reliability (CR) ≥ 0.6. Descriptive statistics and Independent sample t-test and Analysis of Variance (ANOVA) test were performed on the survey data. Students revealed that Business intelligence knowledge is relevant (mean = 4.29, SD = 0.710), has several job opportunities (mean = 4.16, SD = 0.675), and should be integrated into business education curriculum (mean = 3.95.08, SD = 0.79). In addition, there was no statistically significant difference (t (140) = –0.027, p > 0.05) between the concerns of students with Business Intelligence lecture experience and those without. Further, perceived importance and job opportunity significantly, F = 24.601 and p = .000(< .05) relates to the Business intelligence integration in Business Education. The findings draw implications for university management and business institutions in updating curriculum so as to equip business students with the essential Business Intelligence knowledge and skills for the betterment of the business organizations.